Hubungan Antara Pengalaman Belajar Dengan Partisipasi Belajar Di Lembaga Kursus Bahasa Jepang Natsuka Gakkou Kota Padang - Sisry Hermanda; Irmawita Irmawita (Jurnal Family Education, 2022)
This research is motivated by the low learning participation of students at the Natsuka Gakkou Japanese Language Course Institute in Padang City caused by low learning experiences. The objectives of this study are (1) to describe the learning experiences of students at the Natsuka Gakkou Japanese Language Course Institute, Padang City. (2) describes the learning participation of students at the Natsuka Gakkou Japanese Language Course Institute, Padang City. (3) describes the relationship between the learning experience and the participation of students at the Natsuka Gakkou Japanese Language Course Institute, Padang City. This research is a quantitative research with the type of correlational research which aims to examine the correlation between the independent and dependent variables. The population in this study were 28 students. The sampling technique used in this study was cluster random sampling. The sample in this study was 21 students or the sample in this study was 75%. techniques in data collection using written statements (questionnaires) and data collection tools in the form of a list of statements. The data analysis technique uses the percentage formula and data processing uses the Sperman Rho formula. The results of this study indicate that: (1) the learning experience of students at the Natsuka Gakkou Japanese Language Course Institute in Padang City is categorized as low. (2) learning participation at the Natsuka Gakkou Japanese Language Course Institute in Padang City is categorized as low. (3) there is a significant relationship between learning experience and participation in learning at the Natsuka Gakkou Japanese Language Course Institute, Padang City.It is hoped that further researchers will be able to examine new variables so that they can complete the variables in existing research.